1300MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1300MPa-grade nickel-based alloy

By adding optimized content of N elements and purification and smelting technology to the high-temperature superconducting baseband material, combined with strict heat treatment technology, the problem of recrystallization of existing materials in high-temperature environments is solved, and a nickel-based alloy with high tensile strength and elongation is achieved to meet the material needs of high-temperature and high-field superconducting equipment.

CN119753431APending Publication Date: 2025-04-04INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411672542.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing high-temperature superconducting baseband materials are prone to recrystallization in high-temperature environments, resulting in a decrease in tensile strength and cannot meet the development needs of high-temperature and high-field superconducting equipment.

Method used

By adding the optimized content of N elements on the basis of traditional Hastelloy C276, the addition of B elements is avoided, and the O, P, and S content in the alloy is strictly controlled, combined with the heat treatment process of homogenization annealing, forging, hot rolling, solid solution and cold deformation, it is ensured that the N elements are completely dissolved in the alloy matrix.

Benefits of technology

The yield strength of the nickel-based alloy reaches more than 1400MPa, the tensile strength reaches more than 1600MPa, and the elongation rate reaches more than 4.0%. After annealing at 900°C for 5 minutes, the tensile strength reaches more than 1300MPa, the elongation rate reaches more than 15%, and the strong plasticization reaches more than 20GPa·% to meet the needs of the second generation of high-temperature superconducting baseband materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753431A_ABST
    Figure CN119753431A_ABST
Patent Text Reader

Abstract

The invention relates to a 1300MPa-grade nickel-based alloy for a second-generation high-temperature superconducting baseband and a preparation method of the 1300MPa-grade nickel-based alloy, and belongs to the technical field of materials. The high-strength wear-resistant steel comprises the following chemical components in percentage by weight: 15.0%-17.0% of Cr, 15.0%-17.0% of Mo, 3.0%-4.5% of W, 5.0%-7.0% of Fe, 0.3%-0.7% of Mn, 0.01%-0.05% of Si, 0.1%-0.2% of V, 0.1%-0.5% of Co, 0.1%-0.2% of Al, 0.040%-0.080% of N, Clt and the balance of Fe. 0.002%, Plt; 0.005%, Slt; 0.002%, Olt; 0.002%, and the balance being nickel. The purification smelting process is adopted, the oxygen content in the alloy is reduced, the inclusion content is controlled, and the high purity of the material is guaranteed. By adopting the component control strategy, the heat treatment process and the final cold machining preparation, the nickel-based alloy with the yield strength being 1100 MPa or above, the tensile strength being 1300 MPa or above, the ductility being 15% or above and the product of strength and elongation being 20 GPa.% or above can be obtained after annealing is conducted for 5 min at the temperature of 900 DEG C, and the requirements of a second-generation high-temperature superconducting high-performance metal base band are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a 1300MPa nickel-based alloy for a second-generation high-temperature superconducting base tape and a preparation method thereof, belonging to the technical field of materials. Background Art

[0002] Since the discovery of the second-generation superconductor of rare earth barium copper oxide (ReBCO, Re is a rare earth element), it has attracted widespread international attention. The second-generation high-temperature superconductor has the advantages of high transition temperature, complete anti-magnetism, high critical current density and high freezing magnetic field, and has been demonstrated in many fields such as electricity, energy and magnets. The most critical superconducting layer in ReBCO is oxide material with poor ductility. Since its thickness is generally less than 4μm, it is also called coating superconductor.

[0003] The realization of ReBCO superconducting properties requires other multifunctional coatings for protection. Usually, the superconducting layer needs to be epitaxially grown on a flexible metal substrate. Therefore, the basis of ReBCO superconductors is the metal substrate. The buffer layer, superconducting layer and protective layer are all built on the metal substrate. Therefore, the comprehensive performance of the metal substrate determines the quality of ReBCO superconducting properties. Ion beam assisted biaxial texture deposition technology (IBAD) has no specific requirements for the orientation and properties of the metal substrate. The ion capacity and beam current can be adjusted independently. The process is flexible and controllable. It is one of the commonly used methods for commercial preparation of ReBCO superconducting layers. IBAD technology has certain requirements for temperature and atmosphere environment during the preparation of the buffer layer, superconducting layer and protective layer. The optimal preparation process parameters of the superconducting layer are 850℃~900℃. Therefore, the metal substrate is required to have good mechanical properties, non-magnetic or weak magnetism, thermal expansion coefficient corresponding to the superconducting layer, good high-temperature structural stability and excellent oxidation resistance. The currently commercially mature C276 Hastelloy alloy has excellent comprehensive properties and is a widely used substrate material for IBAD technology. The tensile strength of C276 after 50%-90% cold deformation can be above 1300MPa. However, due to the accumulated deformation storage energy of the large cold deformation, it is easy to recrystallize when heated to 850℃~900℃, causing its tensile strength to be lower than 1100MPa. It cannot solve the contradiction between large deformation and recrystallization strength of the material, and therefore cannot meet the current development needs of high-temperature and high-field superconductors, thus limiting the further upgrading of high-temperature superconducting equipment.

[0004] In addition, the Chinese invention patent (application number 202411589006.7) proposes a 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape and its preparation method. Its chemical composition, by weight percentage, is: Cr: 15.0-17.0%, Mo: 15.0-17.0%, W: 4.5-9.5%, Fe: 5.0-7.0%, Mn: 0.3-0.7%, Si: 0.01-0.05%, V: 0.1-0.2%, Co: 0.1-0.5%, Al: 0.1-0.2%, B: 0.001-0.01%, C<0.005%, P<0.005%, S<0.002%, O<0.002%, N<0.002%, and the balance is nickel. Although the tensile strength of the 1500MPa grade nickel-based alloy for high-temperature superconducting base tape after annealing at 900℃ reaches more than 1500MPa, the research found that there are still some shortcomings: when the W content is greater than 4.5%, a more stable nickel-rich and molybdenum-rich P phase and μ phase are formed in the nickel-based alloy, resulting in a higher homogenization and solution treatment temperature, and the cost of metal tungsten is high, and adding too much will greatly increase the cost. In addition, the addition of B to the nickel-based alloy causes the presence of BN in the nickel-based alloy matrix, resulting in the W-rich phase not being completely dissolved in the alloy matrix after homogenization heat treatment, which will reduce the mechanical properties and strength-plasticity product of the alloy after cold deformation.

[0005] With the development of the second generation of high temperature and high field superconductors, higher requirements have been put forward for the operating parameters of key equipment such as high field superconducting magnets prepared therefrom. The metal base tape is required to have a higher strength-plasticity match, and to have good toughness and plasticity while ensuring high strength to meet the winding requirements of the prepared superconductor coils. The tensile strength of the base tape is required to reach more than 1300MPa, and the strength-plasticity product is required to reach more than 20GPa·%. The tensile strength and strength-plasticity product of the current commercial C276 metal base tape cannot meet the current development needs of the second generation of high temperature superconducting metal base tapes. Therefore, in order to upgrade superconducting equipment, it is urgent to develop a new type of nickel-based alloy with excellent toughness and plasticity of 1300MPa for the second generation of high temperature superconductors. Summary of the invention

[0006] The purpose of the present invention is to provide a 1300MPa grade nickel-based alloy for a second-generation high-temperature superconducting base band and a preparation method thereof. On the basis of the traditional Hastelloy C276, by adding an optimized content of N element, not adding B element and strictly controlling the B element content in the alloy, the formation of BN inclusions is avoided, and N is ensured to be completely dissolved into the matrix after the alloy is homogenized and heat treated; by using purified smelting, the O content in the alloy is strictly controlled, the formation of large-sized inclusions is avoided, the high purity of the material is improved, and the occurrence of a belt break accident during the alloy base band processing is avoided; the carbon content is controlled, and homogenization annealing and solution rapid cooling are adopted. The heat treatment process is used to avoid the precipitation of carbides and μ phases; finally, the solid solution N element in the matrix has a high work hardening rate, and a nickel-based alloy with a yield strength of more than 1400MPa, a tensile strength of more than 1600MPa, and an elongation of more than 4.0% can be obtained by cold deformation with a certain deformation amount. After annealing at 900℃ for 5min, the yield strength reaches more than 1100MPa, the tensile strength reaches more than 1300MPa, the elongation reaches more than 15.0%, and the strength-plasticity product reaches more than 20GPa·%, thereby obtaining a second-generation high-temperature superconducting baseband material with excellent strength and plasticity matching.

[0007] The technical solution of the present invention is:

[0008] A 1300MPa grade nickel-based alloy for a second-generation high-temperature superconducting base tape has the following chemical compositions by weight percentage: Cr 15.0-17.0%, Mo 15.0-17.0%, W 3.0-4.5%, Fe 5.0-7.0%, Mn 0.3-0.7%, Si 0.01-0.05%, V 0.1-0.2%, Co 0.1-0.5%, Al 0.1-0.2%, N 0.040-0.080%, C <0.002%, P <0.005%, S <0.002%, O <0.002%, and the balance is nickel.

[0009] The second generation high temperature superconducting base tape uses 1300MPa grade nickel-based alloy, preferably, O<0.001%.

[0010] The method for preparing the 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape comprises the following steps:

[0011] (1) mixing the chemical components in proportion, and obtaining an ingot through purification smelting and electroslag remelting;

[0012] (2) subjecting the obtained ingot to homogenization annealing treatment at high temperature;

[0013] (3) forging the ingot after homogenization annealing;

[0014] (4) The forged alloy ingot is hot rolled: the rolling temperature is 1200°C to 1250°C, the reduction in each rolling pass is controlled to be 20-25%, the total reduction is controlled to be 70-90%, and the hot rolling is followed by water cooling to room temperature;

[0015] (5) Solution heat treatment after hot rolling;

[0016] (6) Cold deformation after solution heat treatment.

[0017] In the method for preparing the 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (2), the temperature of the homogenization annealing treatment is 1250±20°C.

[0018] The method for preparing the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape, in step (3), the forging process is: forging temperature 1200-1250°C, forging ratio above 7.0, and air cooling to room temperature after forging.

[0019] In the method for preparing the 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (5), the solid solution heat treatment process is: keeping the temperature at 1200°C to 1250°C for 2 to 4 hours and then quenching with water to room temperature.

[0020] In the method for preparing the 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (6), the cold deformation process is: cold deformation is performed at room temperature, and the cold deformation amount is 50-90%.

[0021] The preparation method of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape, after cold deformation, the yield strength of the nickel-based alloy reaches more than 1400MPa, the tensile strength reaches more than 1600MPa, and the elongation reaches more than 4.0%; after annealing at 900°C for 5 minutes, the yield strength reaches more than 1100MPa, the tensile strength reaches more than 1300MPa, the elongation reaches more than 15%, and the strength-ductility product reaches 20GPa·%.

[0022] The content range of main elements in the alloy of the present invention is described as follows:

[0023] Cr: Cr is an important element of Hastelloy alloy and the primary element that determines the corrosion resistance of Hastelloy alloy. This is because Cr improves the corrosion resistance of the alloy itself and forms a dense chromium oxide layer on the surface of the material. However, when the Cr content is less than 15wt%, the minimum corrosion resistance required by the alloy cannot be obtained. On the other hand, when the Cr content exceeds 17wt%, Cr-rich intermetallic compounds are easily precipitated, thus forming a chromium-poor zone around the intermetallic compounds, which not only causes the material's hot working properties and mechanical properties to be impaired, but also deteriorates the material's oxidation corrosion resistance. Therefore, in order to ensure that the material has excellent corrosion resistance to most corrosive media in both oxidation and reduction states, the chromium content in the alloy of the present invention is optimized and controlled to be: 15.0-17.0wt%.

[0024] Mo: Molybdenum, like chromium, is a corrosion-resistant element with an ability comparable to that of chromium. The interaction between molybdenum and the corrosive medium will promote the formation of a dense and uniform passivation film on the surface, reduce the possibility of corrosion of the alloy, and significantly improve its corrosion resistance. In addition, Mo can enhance the solid solution strengthening effect of nickel-based alloys, improve the strength and service performance of the alloy. However, excessive Mo content will suffer varying degrees of oxidation during hot working, deteriorating the processing and use performance of the alloy. Therefore, the Mo element with the effect of improving corrosion resistance can be added within the range that does not damage the corrosion resistance, hot workability, weldability and other properties of the material. The content of the Mo element in the alloy of the present invention is optimized and controlled to be: 15.0~17.0wt%.

[0025] W: The role of W is similar to that of Mo, and it mainly plays a role in solid solution strengthening in the alloy system. Since the atomic radius of W is larger than that of Mo, the solid solution strengthening effect is greater than that of Mo. Moreover, due to the high melting point of W, appropriately increasing its content will increase the recrystallization temperature of the alloy after cold working to a certain extent, which is also one of the keys of the present invention. However, too high W will cause the alloy to form a relatively stable nickel-rich and molybdenum-rich μ phase, which cannot be completely eliminated even if the solid solution temperature is maintained for a long time at a very high solid solution temperature. In order to avoid the influence of precipitation on superconducting properties, the content of W needs to be strictly controlled. Therefore, the content of W in the alloy of the present invention is controlled to be: 3.0-4.5wt%, and further optimized to: W3.2-4.2wt%.

[0026] Fe: The addition of iron is mainly to control the cost of the alloy system, because nickel and iron can be infinitely soluble in each other. The addition of Fe replaces the atomic position of Ni, causing the lattice to be distorted, which can play a role in solid solution strengthening to a certain extent. Too much Fe will form Laves phase with Mo and W in the nickel-based alloy matrix, thereby deteriorating the performance of the material. Therefore, the content of iron in the alloy of the present invention is controlled to be: 5.0-7.0wt%.

[0027] Mn: Manganese can enhance the strength and toughness of the alloy through the solid solution strengthening mechanism. Mn replaces the nickel atoms in it, causing distortion, thereby hindering the movement of dislocations and increasing the yield and tensile strength of the material. At the same time, it can significantly reduce the martensite formation temperature M of the alloy. S point, ensuring the stability of the alloy austenite structure. When the Mn content is added too high, it is easy to form MnS inclusions with S in the alloy, and the increase in the volume fraction of the inclusions reduces the impact toughness of the alloy. Therefore, the manganese content in the alloy of the present invention is controlled to be: 0.3-0.7wt%.

[0028] Si: The silicon element plays several key roles: First, as a deoxidizer, Si can effectively reduce the oxygen in the smelting alloy liquid, and react with oxygen to form silicon oxide, thereby improving the purity and overall quality of the alloy; secondly, silicon enhances the strength and hardness of the alloy through the solid solution strengthening mechanism. However, the silicon content needs to be controlled, and too high a silicon content may affect the welding performance of the alloy. Therefore, the silicon content in the alloy of the present invention is controlled to be: 0.01-0.05wt%.

[0029] V: Vanadium is a strong carbide-forming element, which easily forms precipitation phases with carbon and nitrogen in the alloy and pins dislocations. V can fix carbon elements and prevent alloying elements such as Cr from diffusing from the nickel-based alloy matrix into carbides to cause ripening, thereby improving the mechanical strength of the alloy. When the vanadium content is low, it is not easy to fully form fine carbides and cannot play the role of pinning dislocations, while when the content is high, the alloy becomes brittle. Therefore, the vanadium content in the alloy of the present invention is controlled to be: 0.1-0.2wt%.

[0030] Co: Cobalt is basically completely dissolved in the nickel-based alloy matrix, plays a role in solid solution strengthening, and does not form carbides. It forms a synergistic effect with Mo to promote the precipitation of precipitation phases. Cobalt can inhibit the recovery of the dislocation substructure in martensite, provide more nucleation sites for subsequent precipitation phases, and promote precipitation strengthening. Therefore, according to the balancing effect of cobalt on the alloy and its influence on the precipitation effect of the precipitation phase, the content of cobalt in the alloy of the present invention is controlled to be: 0.1-0.5wt%.

[0031] Al: Aluminum is an element that forms the γ′ strengthening phase of the intermetallic compound and is an important element for improving the strength of the alloy. At the same time, the Al content is also an important indicator of the material's resistance to high-temperature oxidation. There is a short-term high-temperature process in the preparation of the second-generation high-temperature superconducting layer, so a higher requirement is placed on the oxidation resistance of the material of the present invention. Therefore, the Al content of the alloy of the present invention is optimized and controlled to be: Al: 0.1-0.2wt%.

[0032] N: In C276 alloy, nitrogen has a significant solid solution strengthening effect. It causes lattice distortion by dissolving in the matrix, increasing the resistance to dislocation movement, thereby improving the strength of the alloy. In addition, nitrogen also inhibits grain growth and dislocation recovery, significantly increases the recrystallization temperature of the alloy, and enhances its stability in high temperature environments. The addition of nitrogen can also reduce the precipitation of brittle second phases, maintain the high temperature strength and corrosion resistance of the alloy, and further improve the comprehensive performance of the C276 alloy. Therefore, the nitrogen content range in the alloy of the present invention is optimized to: N: 0.040~0.080wt%.

[0033] C: Carbon easily forms M with elements such as Cr in alloys 23 C6 carbides will precipitate, especially during the slow cooling process after solutionization. Although carbides precipitate at the original austenite grain boundary interface, they can pin dislocations and hinder the movement of the interface, play a role in precipitation strengthening, and effectively improve the strength of the material. However, the precipitation of these precipitated phases of carbides will affect the superconducting properties of ReBCO, and the carbon content in the alloy needs to be strictly controlled. Therefore, the ultra-low carbon component design idea is adopted, and the C content in the alloy of the present invention is optimized and controlled to: C<0.002wt%.

[0034] S, P: In the production of nickel-based alloys, phosphorus and sulfur are generally regarded as harmful impurities because they can significantly reduce the overall performance of the alloy. P will promote the segregation of W and Mo to form Laves phase, thereby increasing the cold brittleness of the alloy, reducing the cohesion of the grain boundaries, thereby reducing the toughness and plasticity of the material, and will also affect the welding performance, causing the welded joints to be prone to cracks. On the other hand, sulfur will increase the tendency of the material to be hot brittle, especially during processing. At the same time, excessive sulfur will also affect the mechanical processing quality of the material and reduce the strength and toughness of the material. Therefore, the content of sulfur and phosphorus in the alloy of the present invention is extremely strictly controlled: S<0.002wt%, P<0.005wt%.

[0035] O: Oxygen is the main element that produces oxide inclusions in the alloy. Therefore, in order to reduce the inclusions in the alloy and ensure the purity of the material, the oxygen content must be reduced as much as possible. When the oxygen content in the material exceeds a certain limit, especially when the material of the present invention contains a certain amount of Al, continuous brittle oxide inclusions will be formed in the alloy, which will form stress concentration during the processing of the thin strip, resulting in the occurrence of strip breaking accidents. Therefore, the oxygen content in the alloy of the present invention is strictly controlled: O<0.002wt%, further optimized to: O<0.001wt%.

[0036] The innovative design ideas of the present invention are as follows:

[0037] 1) Innovative alloy composition design concept: Based on Hastelloy C276, the present invention adopts an innovative high-nitrogen and boron-free alloy composition design concept to avoid the precipitation of BN, and adopts a matching heat treatment process to ensure that the N element is completely dissolved in the alloy matrix without precipitation of other precipitates, giving full play to the solid solution strengthening effect of N in the alloy; subsequently, in the cold working process, N has a high work hardening rate. After cold working with a cold deformation amount of 50% to 90%, the tensile strength of the material of the present invention reaches more than 1600MPa and the elongation reaches more than 4.0%. Moreover, after annealing at 900℃ for 5min, its tensile strength is still as high as 1300MPa, the elongation is as high as 15%, and the strength-plasticity product reaches more than 20GPa·%. Compared with the current commercial C276 with a tensile strength of 1105MPa, an elongation of 3.5%, and a strength-plasticity product of only 3.9GPa·% after annealing at 900℃ for 5min, the material of the present invention has significantly excellent strength-plasticity matching.

[0038] 2) Matching of hot working and heat treatment system: The nickel-based alloy of the present invention contains 15.0-17.0% of Mo element and 3.0-4.5% of W element. With the addition of N element, the Mo-rich and W-rich μ and P phases in the alloy are more stable. The second-generation superconducting baseband material requires no precipitation phase. The dissolution of the precipitation phase requires a higher heat treatment temperature and holding time, and the higher temperature and holding time will promote the abnormal growth of the material grains. Therefore, ensuring the grain size of the material while no precipitation phase is the second innovation of the present invention. In addition, the material of the present invention is formed once during the forging process at 1200-1250°C, reducing the number of tempering times, thereby ensuring the grain size of the material. At the same time, in the solid solution process, a rapid cooling method is adopted to avoid the precipitation of μ and P phase precipitation phases. The matching between the above hot working and heat treatment systems is adopted to ensure that no precipitation phase is precipitated, while avoiding abnormal growth of the grains of the material of the present invention, thereby realizing the high nitrogen composition design concept of Hastelloy alloy.

[0039] 3) Purification smelting technology: Purification smelting technology is used to strictly control the content of harmful elements such as P, S and O in the alloy that are easy to form inclusions. The O content is controlled below 10ppm, and the P and S contents are controlled below 50ppm and 20ppm respectively, reducing all possibilities of inclusion formation in the alloy and laying a solid foundation for the subsequent preparation of 20-50μm superconducting base tapes.

[0040] 4) Final cold deformation process control: Break the tradition of regulating the heat treatment organization of the material as the final treatment. By controlling the cold deformation amount within 50% to 90%, the grains are further refined, a large number of dislocations are introduced into the nickel-based alloy matrix, and the solid solution N element in the matrix has the effect of increasing the recrystallization temperature of the alloy, ensuring the stability of the material performance during the preparation of the second-generation high-temperature superconducting layer, laying a material foundation for the realization of high-temperature and high-field superconductivity.

[0041] The advantages and beneficial effects of the present invention are:

[0042] 1. The present invention is based on Hastelloy C276, by adding 0.040-0.080wt% of N element in an optimized content, optimizing and matching the subsequent optimized heat treatment system and processing and preparation process, realizing the first application of N element in Hastelloy, and obtaining a high-nitrogen new material with excellent strength and toughness matching: after cold deformation, the tensile strength of the material of the present invention reaches more than 1550MPa, and the elongation reaches more than 3.5%. After annealing at 900℃ for 5min, the tensile strength reaches more than 1300MPa, the elongation reaches more than 15%, and the strength-ductility product reaches 20GPa·%. Compared with commercial C276, it has excellent strength and toughness.

[0043] 2. The present invention adopts purification smelting technology to reduce the oxygen content in the material of the present invention to less than 10ppm. On this basis, the P and S contents in the material are further reduced to ensure that the inclusion content of the material of the present invention is at an extremely low level, further improve the purity of the material, and obtain a nickel-based alloy with high purity and high strength and toughness. Superconducting base strips with a thickness of 20 to 50μm can be stably prepared to meet the material requirements of high-temperature and high-field superconducting equipment.

[0044] 3. The present invention provides a 1300MPa nickel-based alloy and a key preparation process for a second-generation high-temperature superconducting baseband. By adopting the technical solution provided by the present invention, a high-purity new nickel-based high-temperature alloy with excellent comprehensive performance can be stably obtained. The material of the present invention can better support the rapid development of my country's high-temperature and high-field superconducting industry and promote the upgrading of industry equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the cast metallographic structure of Example 1.

[0046] Figure 2 This is a schematic diagram of the metallographic structure of Example 2 after forging.

[0047] Figure 3 Schematic diagram of the metallographic structure of Example 3 after solution treatment at 1250°C.

[0048] Figure 4 Schematic diagram of the metallographic structure of Comparative Example 1 after forging.

[0049] Figure 5 Schematic diagram of the electron probe microscopy (EPMA) element distribution after hot rolling of Comparative Example 2. Among them, (a) is the C element, (b) is the N element, (c) is the W element, and (d) is the Mo element.

[0050] Figure 6 Schematic diagram of the electron probe microanalysis (EPMA) element distribution after solid solution of Comparative Example 3. Among them, (a) is C element, (b) is W element, (c) is N element, (d) is B element, (e) is Mo element, and (f) is Ni element. DETAILED DESCRIPTION

[0051] In the specific implementation process, the present invention further adds N element on the basis of the traditional material C276 Hastelloy alloy, and optimizes the content to 0.040-0.080wt%, matches the optimized hot working and heat treatment system, realizes the complete solid solution of N element in the nickel-based alloy matrix, ensures that the excessive N content brings more stable μ phase and P phase and other precipitation phases in the matrix are completely dissolved back, fully exerts the solid solution strengthening and higher work hardening rate of N in the nickel-based alloy, and further improves the recrystallization temperature and mechanical properties of the nickel-based alloy after cold deformation. In addition, by not adding B content, BN precipitation is avoided, ensuring the complete solid solution of N in the nickel-based alloy matrix during homogenization heat treatment; adopts a pure smelting process to reduce the oxygen content in the alloy, control the inclusion content, and ensure high purity. After cold deformation, the yield strength of the material of the present invention reaches more than 1400MPa, the tensile strength reaches more than 1550MPa, and the elongation reaches more than 4.0%. Moreover, by adopting the above-mentioned composition control strategy, processing and preparation, and heat treatment process, after annealing at 900°C for 5 minutes, the yield strength of the material of the present invention still reaches more than 1100MPa, the tensile strength reaches more than 1300MPa, the elongation reaches more than 15%, and the strength-ductility product reaches more than 20GPa·%, which meets the needs of high-performance metal substrates for second-generation high-temperature superconductors.

[0052] The following examples and drawings will further illustrate the present invention, but are not intended to limit the present invention. The nickel-based alloys in the examples and the alloys in the comparative examples were processed into standard plate-shaped tensile specimens after smelting and heat treatment to test the mechanical properties.

[0053] The preparation process of the 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape of the present invention is: batching → smelting → casting → homogenization → forging and hot working → heat treatment → cold working. Examples 1 to 5 are all prepared by the following method, and the specific steps are as follows:

[0054] (1) mixing the chemical components in proportion, and obtaining an ingot through smelting and electroslag remelting;

[0055] (2) The temperature of the homogenization annealing treatment is 1230° C. to 1270° C. (Examples 1 to 5 are 1230° C., 1250° C., 1270° C., 1245° C. and 1261° C., respectively), and the temperature is kept for 20 to 30 hours (Examples 1 to 5 are 20 hours, 25 hours, 30 hours, 22 hours and 27 hours, respectively), and then air-cooled;

[0056] (3) forging the ingot after homogenization annealing: the forging temperature is 1200° C. to 1250° C. (Examples 1 to 5 are 1200° C., 1250° C., 1225° C., 1235° C. and 1215° C., respectively), the forging ratio is above 7.0 (Examples 1 to 5 are 7.0, 12.0, 10.5, 9.5 and 8.0, respectively), and air-cooling to room temperature after forging;

[0057] (4) The forged alloy ingot is hot rolled: the hot rolling temperature is 1200°C to 1250°C (1200°C, 1250°C, 1230°C, 1215°C and 1240°C for Examples 1 to 5, respectively), the reduction in each rolling pass is controlled to be 20% to 25% (20%, 25%, 21%, 22% and 23% for Examples 1 to 5, respectively), the total reduction is controlled to be 70% to 90%, and the hot rolling is followed by water cooling to room temperature;

[0058] (5) after hot rolling, solution heat treatment is performed: the solution temperature is 1200°C to 1250°C (1220°C, 1210°C, 1250°C, 1230°C and 1240°C in Examples 1 to 5, respectively), the holding time is 2 to 4 h (2.0 h, 3.0 h, 4.0 h, 2.5 h and 3.5 h in Examples 1 to 5, respectively), and then water-cooled to room temperature;

[0059] (6) Cold deformation at room temperature after solution heat treatment: the cold deformation amount is 50-90% (Examples 1-5 are 50%, 60%, 70%, 80% and 90% respectively).

[0060] The present invention is further described in detail below through the accompanying drawings and embodiments.

[0061] Example 1

[0062] In this embodiment, the chemical composition of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr 15.25%, Mo 16.70%, W 3.45%, Fe 5.36%, Mn 0.61%, Si 0.042%, V 0.13%, Co 0.27%, Al 0.15%, N 0.042%, C 12ppm, P 39ppm, S17ppm, O 6ppm, and the balance is nickel.

[0063] Example 2

[0064] In this embodiment, the chemical composition of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr 16.37%, Mo 15.69%, W 3.52%, Fe 6.74%, Mn 0.57%, Si 0.020%, V0.14%, Co 0.23%, Al 0.12%, N 0.079%, C 15ppm, P 31ppm, S18ppm, O 7ppm, and the balance is nickel.

[0065] Example 3

[0066] In this embodiment, the chemical composition of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr 15.73%, Mo 16.48%, W 3.20%, Fe 6.47%, Mn 0.42%, Si 0.037%, V 0.16%, Co 0.35%, Al 0.13%, N 0.060%, C 14ppm, P 28ppm, S10ppm, O 5ppm, and the balance is nickel.

[0067] Example 4

[0068] In this embodiment, the chemical composition of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr 16.50%, Mo 15.35%, W 3.64%, Fe 5.46%, Mn 0.52%, Si 0.045%, V0.18%, Co 0.21%, Al 0.14%, N 0.051%, C 13ppm, P 19ppm, S11ppm, O 4ppm, and the balance is nickel.

[0069] Example 5

[0070] In this embodiment, the chemical composition of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr 16.14%, Mo 15.89%, W 4.20%, Fe 6.90%, Mn 0.35%, Si 0.024%, V0.17%, Co 0.25%, Al 0.11%, N 0.069%, C 12ppm, P 18ppm, S 5ppm, O 5ppm, and the balance is nickel.

[0071] Comparative Example 1

[0072] In this comparative example, no N element is added to the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate by weight percentage, and other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 1.

[0073] Comparative Example 2

[0074] In this comparative example, the nitrogen content of the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate is 0.096% by weight, and the other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 2.

[0075] Comparative Example 3

[0076] In this comparative example, the B content in the 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate is 21ppm by weight, and the other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 3.

[0077] As shown in Table 1, the mechanical properties of the plates of the embodiments and comparative examples after cold rolling are as follows:

[0078] Table 1

[0079] Serial number <![CDATA[Yield strength Rp 0.2 , MPa]]> Tensile strength Rm, MPa Elongation A, % Example 1 1457 1608 6.5 Example 2 1547 1645 4.0 Example 3 1502 1628 5.5 Example 4 1482 1620 6.0 Example 5 1530 1637 4.4 Comparative Example 1 1427 1545 3.6 Comparative Example 2 1564 1671 1.0 Comparative Example 3 1342 1427 2.8

[0080] As can be seen from Table 1, the present invention innovatively adds N element on the basis of the traditional material Hastelloy C276, matches the optimized heat processing process and heat treatment system, ensures that the added N is completely dissolved into the nickel-based alloy matrix, and through a cold rolling reduction of 50-90% deformation, a nickel-based alloy with excellent mechanical properties can be obtained: the yield strength is above 1457MPa, the tensile strength is above 1608MPa, and the elongation is above 4.0%. No N element is added in Comparative Example 1, which is commercial Hastelloy C276. Compared with Example 1, it is found that the yield strength of commercial C276 reaches 1427MPa and the tensile strength reaches 1545MPa, which are lower than the mechanical performance indicators of the material of the present invention. The N content in Comparative Example 2 reaches 0.096%, which is not within the control range of the N element composition of the present invention. Since N is not completely dissolved into the alloy matrix, there are large undissolved phases in the matrix (such as Figure 5 As shown in Figure 2, the mechanical properties are relatively low, especially the elongation is only 1.0%. The B content in Comparative Example 3 is not controlled within the composition requirements of the present invention, resulting in the presence of BN in the alloy matrix (as shown in Figure 2). Figure 6 As shown in the figure, BN acts as a heterogeneous nucleation site, which causes the W-rich phase to not be completely dissolved in the alloy matrix after homogenization heat treatment, resulting in lower mechanical properties.

[0081] As shown in Table 2, the mechanical properties of the cold-rolled plates of the embodiment and the comparative example after annealing at 900°C for 5 minutes and air cooling are as follows:

[0082] Table 2

[0083] Serial number <![CDATA[Yield strength Rp 0.2 , MPa]]> Tensile strength Rm, MPa Elongation A, % Strength and plasticity product, GPa·% Example 1 1156 1324 18.5 24.5 Example 2 1240 1415 15.4 21.8 Example 3 1200 1371 17.1 23.4 Example 4 1180 1349 18.1 24.4 Example 5 1224 1398 16.8 23.5 Comparative Example 1 942 1105 3.5 4.2 Comparative Example 2 1194 1344 2.8 3.8 Comparative Example 3 1079 1211 3.0 3.6

[0084] As can be seen from Table 2, after annealing at 900°C for 5 minutes, the yield strength and tensile strength of the material of the present invention are reduced to a certain extent, but the elongation is greatly improved, wherein the yield strength is above 1156MPa, the tensile strength is above 1324MPa, and the elongation is above 15.4%. This is because N is completely dissolved into the nickel-based alloy matrix, which increases the recrystallization temperature of the nickel-based alloy matrix. After being kept at 900°C for 5 minutes, the cold-rolled nickel-based alloy matrix does not recrystallize, and only a certain degree of dynamic recovery occurs, so the tensile strength of the material of the present invention is still maintained at more than 1300MPa.

[0085] In Comparative Example 1, no N element was added, and the commercial C276 material was recrystallized, and its yield strength reached 942MPa, and its tensile strength was only 1105MPa, with low mechanical properties, and the index did not meet the strength index requirements of the material of the present invention. In Comparative Example 2, since W and Mo were not completely dissolved, its tensile strength was 1344MPa, but its elongation was only 2.8%, and its strength-plasticity product was only 3.8GPa·%, which did not meet the index requirements of the material of the present invention. Similarly, the strength and strength-plasticity product of Comparative Example 3 did not meet the required range, and a precipitated phase was formed along the grain boundary in the microstructure, which reduced the elongation.

[0086] like Figure 1 As shown, the metallographic structure of Example 1 after air cooling of the cast state, it can be seen from the figure that there are a large number of second phases in the structure, which are mainly enriched between the dendrites.

[0087] like Figure 2 As shown in the figure, the metallographic structure of Example 2 after air cooling at 1250°C forging, it can be seen from the figure that after the large deformation one-time forging, the dendrites of the matrix cast structure are effectively broken, and the homogenization and heat preservation stage before forging promote the second phase in the alloy matrix to dissolve back into the matrix. After forging, the alloy structure undergoes partial recrystallization, and the recrystallization area ratio is 13.4%.

[0088] like Figure 3 As shown, the metallographic structure of Example 3 after being kept at 1250°C for 4h. It can be seen from the figure that after homogenization heat treatment, large deformation one-time forging and subsequent 1225°C hot rolling and 1250°C solution treatment, the N in Example 4 is completely dissolved into the alloy matrix, and there is no precipitation phase such as nitride on the grain boundary.

[0089] like Figure 4As shown, the metallographic structure of Comparative Example 1 after air cooling after large deformation and single forging at 1200°C is partially recrystallized, and the recrystallization rate accounts for 23.1%. This is because the N content in the commercial C276 is not within the composition control range of the present invention, so under large deformation storage energy, the recrystallization area ratio is higher than that in Example 2 and Comparative Example 1.

[0090] like Figure 5 As shown, Comparative Example 2 is a schematic diagram of EPMA element distribution after hot rolling. It can be seen from the figure that although the alloy is kept at 1250°C for 4 hours and then hot-rolled and water-cooled to room temperature, there are still large micron-sized particles of undissolved Mo-rich and W-rich phases in the grain boundaries and grains of the alloy matrix. This is because the N content in Comparative Example 2 is as high as 0.096%, which is higher than the N element composition range requirement of the present invention. Although the same processing and heat treatment process as Example 2 is used, there are still undissolved Mo-rich and W-rich phases in the alloy matrix.

[0091] like Figure 6 As shown, Comparative Example 3 is an EPMA schematic diagram after solution treatment at 1250°C for 3 hours. It can be seen from the figure that since the B content is higher than the requirement of the present invention for its composition control, there is a Mo-rich and W-rich phase with BN as the core that has not been dissolved on the grain boundary, resulting in lower mechanical properties and strength-ductility product of Comparative Example 3.

[0092] The mechanical property test results of the above embodiments 1 to 5 show that the 1300MPa grade nickel-based alloy for ReBCO superconducting base tape of the present invention is based on the commercial Hastelloy C276, with an optimized N element content of 0.042 to 0.079% and a W element content of 3.20 to 4.20wt%, and matches the subsequent optimized homogenization treatment, hot working, solution heat treatment (1210°C to 1250°C) and cold working process. After cold rolling with a deformation amount of 50 to 90%, the yield strength reaches 1457MPa or more, the tensile strength reaches 1608MPa or more, and the elongation reaches 4.0% or more. After annealing at 900°C for 5min, the yield strength of the material of the present invention is as high as 1156MPa or more, the tensile strength is as high as 1324MPa or more, the elongation is as high as 15.4% or more, and the strength-ductility product reaches 21.8GPa·% or more. The 1300MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape meets the needs of high-strength and tough metal base tapes for second-generation high-temperature superconductors.

[0093] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A 1300MPa grade nickel-based alloy for second generation high temperature superconducting base tape, characterized in that: Its chemical composition, in weight percentage, is: Cr 15.0-17.0%, Mo 15.0-17.0%, W 3.0-4.5%, Fe 5.0-7.0%, Mn0.3-0.7%, Si 0.01-0.05%, V 0.1-0.2%, Co 0.1-0.5%, Al 0.1-0.2%, N 0.040-0.080%, C<0.002%, P<0.005%, S<0.002%, O<0.002%, and the balance is nickel.

2. The 1300MPa grade nickel-based alloy for the second generation high temperature superconducting base tape according to claim 1, characterized in that: Preferably, O<0.001%.

3. A method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate as claimed in any one of claims 1 to 2, characterized in that: The steps include: (1) mixing the chemical components in proportion, and obtaining an ingot through purification smelting and electroslag remelting; (2) subjecting the obtained ingot to homogenization annealing treatment at high temperature; (3) forging the ingot after homogenization annealing; (4) The forged alloy ingot is hot rolled: the rolling temperature is 1200°C to 1250°C, the reduction in each rolling pass is controlled to be 20-25%, the total reduction is controlled to be 70-90%, and the hot rolling is followed by water cooling to room temperature; (5) Solution heat treatment after hot rolling; (6) Cold deformation after solution heat treatment.

4. The method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 3, characterized in that: In step (2), the temperature of the homogenization annealing treatment is 1250±20°C.

5. The method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 3, characterized in that: In step (3), the forging process is as follows: forging temperature is 1200-1250° C., forging ratio is above 7.0, and air cooling is performed to room temperature after forging.

6. The method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 3, characterized in that: In step (5), the solution heat treatment process is: keeping at 1200°C to 1250°C for 2 to 4 hours and then quenching with water to room temperature.

7. The method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 3, characterized in that: In step (6), the cold deformation process is: cold deformation is performed at room temperature, and the cold deformation amount is 50 to 90%.

8. The method for preparing a 1300MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 3, characterized in that: After cold deformation, the yield strength of the nickel-based alloy reaches more than 1400MPa, the tensile strength reaches more than 1600MPa, and the elongation reaches more than 4.0%; after annealing at 900℃ for 5min, the yield strength reaches more than 1100MPa, the tensile strength reaches more than 1300MPa, the elongation reaches more than 15%, and the strength-plasticity product reaches 20GPa·%.

Citation Information

Patent Citations

  • 1500MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1500MPa-grade nickel-based alloy

    CN119685656A

Cited By

  • 1400 MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1400 MPa-grade nickel-based alloy

    CN119899958A

  • 1200MPa-grade low-cost nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1200MPa-grade low-cost nickel-based alloy

    CN120138435A

  • 1600MPa-grade high-strength nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1600MPa-grade high-strength nickel-based alloy

    CN120249742A

  • High-plasticity and high-strength-ductility nickel-based alloy for second-generation high-temperature superconducting base band and preparation method of high-plasticity and high-strength-ductility nickel-based alloy

    CN120249743A

  • 1400 MPa-grade high-cobalt low-tungsten nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1400 MPa-grade high-cobalt low-tungsten nickel-based alloy

    CN120555833A